Microbial studies on Aisa a potential indigenous laboratory fermented food condiment from Albizia saman (Jacq.)F. Mull (2005)
A total of 134 bacterial isolates characterized as Bacillus cereus var. mycoides, B. coagulans, B. licheniformis, B. megaterium, B. pumilus, B. subtilis, Staphylococcus cereus and S. saprophyticus were isolated from fermenting Albizia saman seeds during the laboratory production of aisa, a potential food seasoning condiment. Bacillus species were the most predominant species and produced the highest ammoniacal smell characteristic of typical indigenous fermented food condiments. There was a general increase in the microbial population throughout the fermentation period. The pH of the fermenting mash was between 6.5-8.2. The physical observation of the fermented mash was dark brown in appearance with creamish mucilaginous slime, moulding the fermented cotyledons together. Process optimization of the fermenting aisa mash indicated optimal fermentation temperature of 45°-50°C, optimal pH of 6.9-8.2, while the fermented mash with pawpaw leaves gave the most accepted product as compared to banana leaves, local leaves and almond leaves. Consumers gave 74.0%-96.0% preference to aisa as an alternative to iru and ogiri, the most popular indigenous fermented food condiments in Nigeria. In comparison with the laboratory fermented samples, Escherichia coli, Klebsiella pneumoniae, Enterobacter aerogenes and Proteus mirabilis were isolated in addition to the Bacillus and Staphylococcus species in the traditionally fermented aisa samples. Fermentation of Albizia saman seeds for 5-7 days gave the best organoleptic parameters of aisa even after 3 months of storage at ambient temperature and 6 months storage at 4°C in the refrigerator.